Legal Protection of the Bensu in Trademark from an Intellectual Property Perspective (Case Study of Central Jakarta District Court Decision 57/Pdt.Sus-Hki/Mark 2019/Pn Niaga Jkt.Pst) - Rahmayani, Rahmayani; Sendy, Beby (Universitas Syiah Kuala, 2025)
Trademark disputes reflect one of the intellectual property law conflicts that have attracted widespread attention in Indonesia. One of them is the Bensu trademark dispute involving Ruben Samuel Onsu, a public figure and PT Ayam Geprek Bensu Sujono, a business entity that claims exclusive rights to use the name